Enhancing Writing Ability of Students through Multiple Drafts and Critical Comments - Kandel, Purna Bahadur (Tribhuvan University Journal, 2016)
This is an exploratory study through which the researcher conducted the research based on survey research design to find out the existing practices of providing feedbacks and perceptions of faculties in developing writing through multiple drafts and critical comments at B.Ed. level. Fifty respondents were selected from constituent and affiliated colleges as informants adopting purposive non-random sampling procedure to collect data. Questionnaire and informal interview were administered as tools to elicit the data for this study. It was found that the practice of brainstorming, planning, writing multiple drafts, revising and editing can enhance writing skills. The writing of multiple drafts facilitates the students to use mechanics and orthography adequately and develop cohesive and coherent writing. Moreover, it was found that students need teachers’ written as well as oral comments and feedbacks in developing writing skills; teachers’ critical written feedback and comments are more effective than oral feedback and most of the learners rarely keep on writing multiple drafts in the most of the colleges at the Tribhuvan University.